The Relationship between Job Attachment, Cultural Intelligence, and Organizational Citizenship Behavior among Shiraz Municipality Employees - Razavi, Shohreh; Hooman, Farzaneh (International Journal of Applied Behavioral Sciences, 2025)
Background and Aim: organizational citizenship behaviors (OCBs) contribute to a more positive and productive work environment. Understanding what factors influence OCB allows organizations to develop strategies to promote these desirable behaviors. This study aimed to predict OCB based on job attachment and cultural intelligence among Shiraz municipality employees. Materials and Methods: The research method was descriptive-correlational. The research population consisted of all 303 employees of the Shiraz Municipality's Cultural-Social Organization in 2023. 108 employees were selected using a convenience sampling method. Data were collected using questionnaires for OCB, job attachment, and cultural intelligence. Data were analyzed using descriptive statistics, Pearson's correlation coefficient, and stepwise regression. Results: The results showed significant positive relationships between job attachment and OCB (P<0.01) and cultural intelligence and OCB (P<0.01). Additionally, there was a multiple relationship between job attachment, cultural intelligence, and OCB among Shiraz municipality employees (P<0.01). Conclusion: These findings suggest that employees with higher levels of job attachment and cultural intelligence are more likely to engage in OCBs. This study contributes to the understanding of factors influencing employee OCB by highlighting the importance of both affective (job attachment) and cognitive (cultural intelligence) factors.